Psychometric properties of the Chinese version of scales of knowledge, attitude, and practice of self-care for patients with arteriovenous fistula: a translation and verification study - Chuang Li; Chuang Li; Youbei Lin; Jiaxin Cheng; Danfeng Xu; Danfeng Xu; Lan Zhang (Frontiers in Public Health)
BackgroundChronic kidney disease (CKD) represents a significant global public health challenge, characterized by its high prevalence and the complexity of its treatment, which collectively impose substantial burdens on patients’ quality of life and healthcare systems. Hemodialysis remains a critical life-sustaining treatment for CKD patients, with arteriovenous fistulas (AVFs) being the most commonly used vascular access. The long-term functionality of AVFs relies heavily on patients’ self-care abilities, encompassing their knowledge of maintenance practices, appropriate attitudes toward care, and the implementation of effective self-care behaviors. Consequently, accurately assessing the self-care capabilities of patients with AVFs is essential for optimizing treatment outcomes and enhancing their overall quality of life.ObjectiveThis study aims to translate the scales of knowledge, attitude, and practice of self-care for patients with arteriovenous fistula (SKAPS-AVF) into Chinese and evaluate its psychometric properties among Chinese patients to ensure its validity and reliability in clinical and research settings.MethodThe study employed the Brislin translation model to translate and back-translate the original scale, followed by cultural adaptation to ensure its relevance to the Chinese context. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted to assess the structural validity of the scale. Reliability was evaluated by calculating Cronbach’s alpha, split-half reliability, and McDonald’s Omega (Ω) to determine the internal consistency and stability of the scale.ResultsExploratory factor analysis (EFA) revealed that the translated scale has a three-factor structure, with eigenvalues greater than 1 for all factors and a total variance explanation rate of 63.099%. Confirmatory factor analysis (CFA) demonstrated good model fit, with fit indices such as the chi-square value, Comparative Fit Index (CFI), Tucker–Lewis Index (TLI), and Root Mean Square Error of Approximation (RMSEA) meeting acceptable standards. Reliability analysis indicated that Cronbach’s alpha, split-half reliability, and McDonald’s Omega values all exceeded 0.7, suggesting good internal consistency and stability of the scale.ConclusionThe C-SKAPS-AVF demonstrated good psychometric properties, with high structural validity and reliability, making it a robust tool for assessing self-care capabilities in patients with arteriovenous fistulas. This scale provides a reliable measurement tool for related clinical interventions and research. However, future studies should consider expanding the sample size and evaluating the scale’s longitudinal stability and applicability across different cultural contexts.